2014
DOI: 10.1080/13602004.2014.911583
|View full text |Cite
|
Sign up to set email alerts
|

Muslims in France and Great Britain: Issues of Securitization, Identities and Loyalties Post 9/11

Abstract: The September 11, 2001 attacks in the United States have liberated an encompassing rhetoric globally which designates all that is 'Muslim' or perceived to be such as a threat. The securitizing perspective, intertwined with debates over Muslims' integration and increasingly visible religiosity has led to growing suspicions regarding Muslims' loyalties in Europe. This analysis seeks to characterize this securitizing perspective and considers on the one hand, the inherent equalisation of increasing Muslim identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…For example, the Islamic revolution in Iran led Islam to be perceived as directly incompatible with democracy. 18 Islam has been interpreted to conflict with freedom of expression in the popular imagination as a result of the Rushdie Affair, the Danish Cartoon Crisis and the Charlie Hebdo Crisis. Similarly, the prohibition of apostasy and debates surrounding secularism have led Islam to be constructed as incompatible with freedom of religion within Europe.…”
Section: The Construction Of Migrants As a Threatmentioning
confidence: 99%
“…For example, the Islamic revolution in Iran led Islam to be perceived as directly incompatible with democracy. 18 Islam has been interpreted to conflict with freedom of expression in the popular imagination as a result of the Rushdie Affair, the Danish Cartoon Crisis and the Charlie Hebdo Crisis. Similarly, the prohibition of apostasy and debates surrounding secularism have led Islam to be constructed as incompatible with freedom of religion within Europe.…”
Section: The Construction Of Migrants As a Threatmentioning
confidence: 99%
“…After several attacks by asylum seekers, Germany has gone through its processing mechanism for recently arrived migrants, refugees, and asylum seekers (Faiola, A & Kirchner, S, 2016). Campaigns against mass immigration and, inevitably, the "Islamization" of the Europe, with the latter being perceived as a security concern and a threat to "Western values" (Ajala, 2014) Waever (2003 asserts that powerful and well-known Muslims experience hatred from the non-believing actors. It features actors who contend that Islam threatens secular norms, political norms, and European values (existential danger), and that justifies extraordinary actions against it.…”
Section: Islamophobia As a Security Threat Dimensionmentioning
confidence: 99%
“…The 'high policing tactics' that are often linked to securitisation, and which have become embedded in everyday policing practice, can be experienced by the public, and particularly minority groups, as threatening, humiliating, intrusive and insensitive (see Jonathan-Zamir, Hasisi, and Margalioth 2016, 613-614). Several studies in various contexts have demonstrated how processes of securitisation, and the counter-terrorism policies and practices used in the pursuit of security, can have a discriminatory, stigmatising, marginalising or alienating effect, creating and sustaining 'suspect communities' in the climate of prevailing terrorist threats (see Hickman et al 2007;Brown 2008;Breen Smyth 2009;Pantazis and Pemberton 2009;Spalek 2010Spalek , 2011Awan 2012;Mythen 2012;Mythen, Walklate, and Khan 2013;Ajala 2014;Vermeulen 2014). Certainly, the ethics and morality of securitisation are of interest to scholars, practitioners and the general public (Floyd 2016, 80-82).…”
Section: The Securitisation Of the Museummentioning
confidence: 99%